Strategy involving stakeholders and government to contribute and to implement the ILEDSA. Issue 1 (March 2021) - Subhan; Umam, A H; Muslih, A M; Rasyid, U H A; Farida, A; Anhar, A
Abstract: A low emission development strategy (LEDS) is designed to develop action programs and policies to place a country on a development pathway that is resilient to climate change while working towards measurable long-term reduction of greenhouse gas emissions. Aceh's efforts to protect forests have shown a steady rate of reduction in deforestation from 2013-2017. However, the threat still exists, so that an integrated strategy with other sectors is needed to ensure that the goals of tackling climate change and reducing deforestation can be achieved. The data sources for this study are primary and secondary in nature and were carried out by following the basic structure of the 'SWOT' analysis (Strengths, Weaknesses, Opportunities and Threats). Some of the strategies produced in this study to involve stakeholders and government are: 1) District, Provincial and National level governments implement policies and regulations that are synergistic between institutions; 2) Traders, Exporters / Cooperatives and Collectors monitor the performance of certified coffee and overcome market failures; 3) The Gayo Coffee Protection Society (MPKG), Universities and Research Institutions apply Geographical Indications in every export product and support research funds; and 4) Coffee farmers / planters undertake technological interventions, develop market-based strategies, and develop risk management schemes.